IGF-1 preserves salivary gland function following fractionated radiation - Limesand, Kirsten H. (2010)
PURPOSE: Radiotherapy for head and neck cancer consists of fractionated radiation treatments that cause significant damage to salivary glands leading to chronic salivary gland dysfunction with only limited prevention and treatment options currently available. METHODS AND MATERIALS: Mouse models were exposed to fractionated radiation and salivary gland function and histological analyses of structure, apoptosis, and proliferation were evaluated. RESULTS: In this study, we report that treatment with fractionated doses of radiation results in a significant level of apoptotic cells in FVB mice after each fraction, which is significantly decreased in transgenic mice expressing a constitutively active mutant of Akt1 (myr-Akt1). Salivary gland function is significantly reduced in FVB mice exposed to fractionated radiation; however myr-Akt1 transgenic mice maintain salivary function under the same treatment conditions. Injection of recombinant IGF-1 into FVB mice, which activates endogenous Akt, suppresses acute apoptosis and preserves salivary gland function following fractionated doses of radiation 30–90 days after treatment. FVB mice exposed to fractionated radiation have significantly lower levels of PCNA positive salivary acinar cells 90 days after treatment which correlates with a chronic loss of function. In contrast, FVB mice injected with IGF-1 prior to each radiation exhibit acinar cell proliferation rates similar to untreated controls. CONCLUSION: These studies suggest that activation of IGF-1 mediated pathways prior to head and neck radiation could modulate radiation-induced salivary gland dysfunction and maintain glandular homeostasis.